2016
DOI: 10.1111/1758-2229.12484
|View full text |Cite
|
Sign up to set email alerts
|

RNA‐Seq identifies redox balance related gene expression alterations under acute cadmium exposure in yeast

Abstract: The nonessential metal cadmium can cause cell toxicity and is associated with a range of human diseases including cardiovascular diseases, neurodegenerative diseases and cancers. In this study, cadmium-induced global gene expression profile of yeast was obtained using RNA Sequencing (RNA-Seq) and further analyzed by means of informatics and experiments. A total of 912 Differentially Expressed Genes (DEGs) (FDR of q < 0.01), including 415 Cd-inducible and 497 Cd-repressed genes were identified. Based on the DEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…We first tested the effect of CdCl2 exposure on Pol II association by ChIP-seq ( Figure 6A). Marked induction of Pol II association was observed with the 47 genes showing the largest increase in mRNA abundance upon CdCl2 exposure (Momose and Iwahashi 2001), while association of Pol II with RP genes decreased to near baseline levels, in agreement with previous studies showing suppression of RP gene mRNA species upon CdCl2 exposure (Momose and Iwahashi 2001;Hosiner et al 2014;Huang et al 2016). Promoters showing at least 3-fold increase in normalized Pol II occupancy upon CdCl2 administration, and from the top 1000 Pol II-occupied genes after CdCl2 exposure, overlapped strongly with those identified in microarray studies (data not shown) (Momose and Iwahashi 2001).…”
Section: Effect On Pol II and Mediator Occupancy Of Exposure To Cadmiumsupporting
confidence: 91%
See 2 more Smart Citations
“…We first tested the effect of CdCl2 exposure on Pol II association by ChIP-seq ( Figure 6A). Marked induction of Pol II association was observed with the 47 genes showing the largest increase in mRNA abundance upon CdCl2 exposure (Momose and Iwahashi 2001), while association of Pol II with RP genes decreased to near baseline levels, in agreement with previous studies showing suppression of RP gene mRNA species upon CdCl2 exposure (Momose and Iwahashi 2001;Hosiner et al 2014;Huang et al 2016). Promoters showing at least 3-fold increase in normalized Pol II occupancy upon CdCl2 administration, and from the top 1000 Pol II-occupied genes after CdCl2 exposure, overlapped strongly with those identified in microarray studies (data not shown) (Momose and Iwahashi 2001).…”
Section: Effect On Pol II and Mediator Occupancy Of Exposure To Cadmiumsupporting
confidence: 91%
“…To this end, we chose to examine the effect of exposure to CdCl2. Exposure to this toxic metal at sub-millimolar concentrations induces a rapid transcriptional response in which ~150-500 genes are induced and from 18 to ~400 genes repressed (Momose and Iwahashi 2001;Cormier et al 2010;Hosiner et al 2014;Huang et al 2016). Induced genes are enriched for binding sites for Hsf1, Msn2, and Msn4, and genes involved in ribosomal biogenesis are repressed by CdCl2 exposure, in common with the response to heat shock and other environmental stresses (Gasch et al 2000;Causton et al 2001;Hosiner et al 2014).…”
Section: Effect On Pol II and Mediator Occupancy Of Exposure To Cadmiummentioning
confidence: 99%
See 1 more Smart Citation
“…Their study revealed anti-oxidative genes ( GRX2 ) and redox homeostasis genes ( TRR1 , TRR2 , and TRX2 ) to be upregulated in response to CdCl 2 exposure, due to potential release of Cd 2+ ions [26]. Interestingly, cadmium is not redox-active, which means it cannot generate ROS directly, yet, Cd-induced ROS is a commonly observed response [27]. They pointed out that metals, such as As 3+ , Cd 2+ , and Hg 2+ , had an affinity toward thiol groups (-SH), which play disparate roles in the function of enzymes, transcription factors, and membrane proteins [26].…”
Section: Introductionmentioning
confidence: 99%
“…Inspired with the above facts, here we have synthesized some macrocyclic complexes where the d 10 metal are introduced in the core lipophilic moiety, which can favour the loading of different healing agents and at the same time the availability of metal ions are also limited. The macrocyclic ligand was synthesized by Schiff base condensation reaction and further treated with two metal ions, a bio friendly main group metal ion Mg(II) and a biologically not so accepted transition metal ion Cd(II), to get the metal‐ macrocycle complexes (Scheme ). Mg(II) forms one complex, [L1 4– (Mg 2+ ) 2 ] ( 1 ) where Cd (II) forms a mixture of two non‐separable complexes, [L1 4– (Cd 2+ ) 2 (H 2 O) 2 ] ( 2 ) and [H 2 L1 2– Cd 2+ ] ( 3 ).…”
Section: Introductionmentioning
confidence: 99%